Early Childhood Caries - A Continuing Oral Health Problem: A Review - B. Kowash, Mawlood (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2014)
Early Childhood Caries (ECC) is a chronic, transmissible infectious disease affecting the primary teeth. The etiology of the condition is a combination of factors including frequent consumption of fermentable carbohydrates as liquids, especially when the baby is sleeping, with on-demand breast- or bottle-feeding. Other factors include oral colonization by cariogenic bacteria (especially mutans streptococci), poor oral hygiene and poor parenting. It is the most common chronic disease among children. The prevalence of ECC in infants and preschool children has been reported to vary between 3% and 94% world-wide. ECC can result in considerable suffering, pain, disfigurement and frequently compromises future dentition. This ultimately leads to a reduction in the quality of life of affected children. This paper provides an updated review of ECC. Its terminology, etiology, prevalence, clinical picture, complications and management are critically discussed and a solution to the continuing problem of ECC is suggested.
Keywords: diet